My Words Flew Away Like Birds - Pearson, Debora; Jain, Shrija, 1993- (Toronto : Kids Can Press, 2021)
"My Words Flew Away Like Birds is both a poignant and heartening story about the experience of a child who moves to a new country. Everything feels new and strange to her, and though she has learned some of the language, when she tries to speak, all her words fly away. In the end, our heroine finds she doesnt need a lot of words to make a new friend. It is a story of finding a sense of belonging in a new place, resilience, and human connection. An utterly charming and sensitive portrayal of a childs immigrant experience."--
""When I came here, all my words flew away." As her family is getting ready to move to a different country, a little girl learns words in a new language. "Hello, how are you?" "I am very well, thank you." "Goodbye!" But in the new place, everyone speaks so fast, their words tumble and swirl all around. Their words dont sound like the ones the girl learned. So she doesnt say anything. She waits, watches and listens. Until one day, she discovers she doesnt need a lot of words to find her way." --
Keywords: Belonging (Social psychology) -- Juvenile fiction; Immigrant children -- Juvenile fiction; Friendship -- Juvenile fiction; Moving, Household -- Juvenile fiction; Belonging (Social psychology) -- Fiction; Immigrant children -- Fiction; Friendship -- Fiction; Moving, household -- Fiction; Fiction; Picture books